Exploring Growth Effects of Industrial Unrest in Nigeria - Osazuwa, Solomon O; Edeme, Richardson Kojo (Jurnal Ekonomi dan Studi Pembangunan, 2018)
This study empirically explores growth effects of industrial unrest in Nigeria using both aggregated and disaggregated approach. The estimated results for the aggregate economy reveal that strikes and lock-outs negatively affect the economy. On the education sector, the results show that on the average, increasing the days of strike by an additional day reduces output from the education sector. The estimated coefficients for the health sector also shows that man day lost due to industrial unrest negatively affect, albeit marginally, the growth of the sector. For the mining sector, the results reveal that none of the measure of industrial unrest is statistically significant. The estimates for the construction sector reveal that every additional strike or lock-out experienced reduces the sectorâs output. As further revealed by the results, increasing the number of workers on strike in the agricultural sector reduces the sectorâs output. Overall, industrial unrest reduced output by 8.3 percent which dampened economic growth by 0.6 percent. Since empirical evidence from this study reveal that strikes and lock-outs affects different sectors of the economy differently, government and relevant stakeholders should develop sector-specific approaches in addressing and managing the issues of industrial unrest in the economy.